Fabrication of Sub‐Micrometer‐Thick Solid Electrolyte Membranes of β‐Li3PS4 via Tiled Assembly of Nanoscale, Plate‐Like Building Blocks. Issue 21 (7th May 2018) - Hood, Zachary D.; Wang, Hui; Pandian, Amaresh Samuthira; Peng, Rui; Gilroy, Kyle D.; Chi, Miaofang; Liang, Chengdu; Xia, Younan
Abstract: Solid electrolytes represent a critical component in future batteries that provide higher energy and power densities than the current lithium‐ion batteries. The potential of using ultrathin films is among the best merits of solid electrolytes for considerably reducing the weight and volume of each battery unit, thereby significantly enhancing the energy density. However, it is challenging to fabricate ultrathin membranes of solid electrolytes using the conventional techniques. Here, a new strategy is reported for fabricating sub‐micrometer‐thick membranes of β‐Li3 PS4 solid electrolytes via tiled assembly of shape‐controlled, nanoscale building blocks. This strategy relies on facile, low‐cost, solution‐based chemistry to create membranes with tunable thicknesses. The ultrathin membranes of β‐Li3 PS4 show desirable ionic conductivity and necessary compatibility with metallic lithium anodes. The results of this study also highlight a viable strategy for creating ultrathin, dense solid electrolytes with high ionic conductivities for the next‐generation energy storage and conversion systems. Abstract : Sub‐micrometer‐thick membranes of β‐Li3 PS4, a promising solid electrolyte for Li‐metal batteries, are fabricated for the first time with nanoscale, plate‐like building blocks composed of Li3 PS4 ·2ACN. The solid electrolyte membranes offer high ionic conductivity, good thermal stability, and compatibility with metallic lithium anode.